2022
DOI: 10.3390/aerospace9020058
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Bayesian Model of Aircraft Encounters in the Terminal Area Given a Straight Takeoff or Landing

Abstract: The integration of new airspace entrants into terminal operations requires design and evaluation of Detect and Avoid systems that prevent loss of well clear from and collision with other aircraft. Prior to standardization or deployment, an analysis of the safety performance of those systems is required. This type of analysis has typically been conducted by Monte Carlo simulation with synthetic, statistically representative encounters between aircraft drawn from an appropriate encounter model. While existing en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This also means that airspace and safety conformance monitoring services need to be available ensuring safe conditions during all phases of the active flight. Since UAM operations are not yet conducted on a daily basis, the UAM and U-space/UTM community might consider emerging ideas proposed for traditional aviation such as [166][167][168][169][170][171].…”
Section: Tactical Measuresmentioning
confidence: 99%
“…This also means that airspace and safety conformance monitoring services need to be available ensuring safe conditions during all phases of the active flight. Since UAM operations are not yet conducted on a daily basis, the UAM and U-space/UTM community might consider emerging ideas proposed for traditional aviation such as [166][167][168][169][170][171].…”
Section: Tactical Measuresmentioning
confidence: 99%
“…Lascara et al suggested four concept components that could enable the routine integration of UAM traffic in existing terminal area airspace [22]. Another similar study was conducted by Weinert, A. et al [23], who suggested an initial model of terminal operations in which an aircraft landing or taking off via a straight trajectory encounters another aircraft and evaluated the detection and avoidance systems. A small number of studies related to the trajectories or the collision avoidance of individual aircraft for the operation of UAM have been performed.…”
Section: Related Work and Previous Researchmentioning
confidence: 99%